Gender differences in e-learning satisfaction - González-Gómez, Francisco; Guardiola, Jorge; Martín Rodríguez, Óscar; Montero Alonso, Miguel Ángel (Computers and education, 2012)
Student learning skills differ depending on gender. The importance of studying this situation in the classroom is that recommendations can be made taking gender into consideration. In e-learning, the roles of students and teachers change. In line with recent research, the question this paper raises is whether or not gender differences also exist in e-learning. The main contribution this research makes to the literature is to provide evidence on the issues male and female students consider important in their assessment of e-subjects. This study is based on a sample of 1185 students who are doing on-line courses at the Universidad de Granada in Spain. The main conclusion is that female students are more satisfied than male students with the e-learning subjects that make up the sample. Furthermore, we find that female students assign more importance to the planning of learning, as well as to being able to contact the teacher in various ways. ► We study the differences of male and female students in e-subjects assessment. ► Female students are more satisfied than male students in the e-learning subjects. ► Female give more importance to planning of learning and contact with the teacher.